Distribution of Age, Stage, and Histopathology of Cervical Cancer: A Retrospective Study on Patients at Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia, 2006-2010 - Anggraeni, Tricia D. (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To review the distribution of age, stage at presentation, and histology of cervical cancer at Dr. Cipto Mangunkusumo Hospital. Materials and methods: This cross sectional study involved 2297 subjects with cervical cancer at Dr. Cipto Mangunkusumo Hospital and registered at the Cancer Registration Information System during 5 years period from January 2006 to December 2010. Histotype was confirmed by histopathology examination. The International Federation of Gynecology and Obstetrics (FIGO) classification was used to stage the disease. Result: The mean age of cervical cancer patients was 51.42 years old (SD 9.694, range 21 - 85). The highest incidence was in 35 - 64 years (87.3%), with the peak incidence in 40 - 59 years (71.3%). There were 0.4 % patients identified at stage IA1, 0.1% at stage IA2, 7.3% at stage IB1, 4.9% at stage IB2, 10.5% at stage IIA, 17.3% at IIB, 1.7% at stage IIIA, 50.2% at stage IIIB, 4.3% at stage IVA, 3.2% at stage IVB. Of the 2297 patients, 70.2% had epidermoid carcinoma, 15.1% had adenocarcinoma, 10.2% had adenosquamous, 0.6% had clear cell, 3.9% had other types. Conclusion: A large proportion of cervical cancer (76.7%) presented in advanced stage (â¥ stage IIB). The highest incidence (57.8%) was in the age range 45 - 59 years. Squamous cell carcinoma is the most frequent histopathology type (70.2%), followed by adenocarcinoma (15.1%) and adenosquamosa (10.2%). A lack of effective screening programs aimed at detecting and treating precancerous conditions is a key reason for the high incidence of cervical cancer at advanced stage. [Indones J Obstet Gynecol 2011; 35-1: 21-4] Keywords: cervical cancer, age, stage, histopathology